Pentingnya Pelatihan Dan Pengembangan Sumberdaya Manusia Bagi Organisasi Di Suatu Perusahaan - Mirantih; Ahmad Gunawan (Jurnal Ekonomi dan Bisnis Digital, 2023)
This research aims to increase employee productivity and help them achieve maximum organizational goals more quickly. The research was taken from an industrial company in the manufacturing sector in the Cikarang area using numbers or quantitative forms. Human resource development is very necessary because it has aspects The important thing is regarding selection, recruitment, orientation, training, development, performance assessment and termination of employment. In this research, research was carried out in the production and quaty operator section which aims to improve human resource development for the Company's organization. Every month there is always a gradual evaluation of each department in order to develop employee productivity in the Company